Clostridioides difficile Toxin CDT Induces Cytotoxic Responses in Human Mucosal-Associated Invariant T (MAIT) Cells - Marquardt, Isabel; Jakob, Josefine; Scheibel, Jessica; Hofmann, Julia Danielle; Klawonn, Frank; Neumann-Schaal, Meina; Gerhard, Ralf; Bruder, Dunja; Jänsch, Lothar (Frontiers in Microbiology, 2021)
Clostridioides difficile is the major cause of antibiotic-associated colitis (CDAC) with increasing prevalence in morbidity and mortality. Severity of CDAC has been attributed to hypervirulent C. difficile strains, which in addition to toxin A and B (TcdA, TcdB) produce the binary toxin C. difficile transferase (CDT). However, the link between these toxins and host immune responses as potential drivers of immunopathology are still incompletely understood. Here, we provide first experimental evidence that C. difficile toxins efficiently activate human mucosal-associated invariant T (MAIT) cells. Among the tested toxins, CDT and more specifically, the substrate binding and pore-forming subunit CDTb provoked significant MAIT cell activation resulting in selective MAIT cell degranulation of the lytic granule components perforin and granzyme B. CDT-induced MAIT cell responses required accessory immune cells, and we suggest monocytes as a potential CDT target cell population. Within the peripheral blood mononuclear cell fraction, we found increased IL-18 levels following CDT stimulation and MAIT cell response was indeed partly dependent on this cytokine. Surprisingly, CDT-induced MAIT cell activation was found to be partially MR1-dependent, although bacterial-derived metabolite antigens were absent. However, the role of antigen presentation in this process was not analyzed here and needs to be validated in future studies. Thus, MR1-dependent induction of MAIT cell cytotoxicity might be instrumental for hypervirulent C. difficile to overcome cellular barriers and may contribute to pathophysiology of CDAC.